Outcomes of Microdiscectomy Versus Conventional Discectomy (Medical Forum Monthly, 2023)
Objective: Comparison of post-operative infection rate and back and leg pain on visual analogue scale in microdiscectomy versus conventional open discectomy.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Neurosurgery ward Bahawal Victoria Hospital Bahawalpur from January 2023 to June 2023.Materials and Methods: This study has been conducted with the collaboration of orthopedic surgeons and neurosurgeons. 60 study cases with symptomatic herniated lumbar disc were equally divided into two groups (30 cases in each group). One group underwent microdiscectomy while other group underwent open conventional discectomy. Outcomes in terms of post-operative infection rate and relieve in back and leg pain on visual analogue pain scale were compared of both groups. Adult patients of either gender were included in this study.Results: Age of the study cases was 16-70 years with mean age of 48.37 ± 2.1 years. There were 34(56.7%) male and 26(43.3%) female cases. In 21(70%) cases of Group-A hospital stay was <5 days and in 9(30%) cases > 5 days. While in Group-B hospital stay was <5 days in all the cases (100%). In Group-A wound infection was reported in 3(10%) cases as compared to 1(3.3%) in Group-B. Mean improvement in lower back pain and leg pain on visual analogue scale (VAS) was higher in Group-B versus Group-A (4.7 ± 1.2 vs. 3.6 ± 1.5, P <0.001).Conclusion: Both surgical techniques are good but lower infection rate and significant improvement in pain was reported in microdiscectomy versus open discectomy.